2010
DOI: 10.1021/tx100146v
|View full text |Cite
|
Sign up to set email alerts
|

DNA Oligomers Containing Site-Specific and Stereospecific Exocyclic Deoxyadenosine Adducts of 1,2,3,4-Diepoxybutane: Synthesis, Characterization, and Effects on DNA Structure

Abstract: Abstract1,2,3,4-Diepoxybutane (DEB) is a carcinogenic metabolite of 1,3-butadiene (BD), an important industrial and environmental chemical present in urban air and in cigarette smoke. DEB is considered the ultimate carcinogenic species of BD due to its potent genotoxicity and mutagenicity attributed to its ability to form DNA-DNA cross-links and exocyclic nucleoside adducts. Mutagenesis studies suggest that DEB adducts formed at adenine bases may be critically important, as it induces large numbers of A → T tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(47 citation statements)
references
References 43 publications
(87 reference statements)
3
44
0
Order By: Relevance
“…28,29 DNA strands containing ( R,R )- N 6 -(2-hydroxy-3,4-epoxybutan-1-yl)-dA were converted to the corresponding ( R,S )-1, N 6 -HMHP-dA containing strands via intramolecular nucleophilic substitution in an aqueous solution. 28,29 These reactions were conducted on solid support in order to maximize the yield of the final product. All synthetic oligodeoxynucleotides were purified by HPLC to achieve > 98% purity and characterized by liquid chromatography-mass spectrometry (Table 1, Supplement S-1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…28,29 DNA strands containing ( R,R )- N 6 -(2-hydroxy-3,4-epoxybutan-1-yl)-dA were converted to the corresponding ( R,S )-1, N 6 -HMHP-dA containing strands via intramolecular nucleophilic substitution in an aqueous solution. 28,29 These reactions were conducted on solid support in order to maximize the yield of the final product. All synthetic oligodeoxynucleotides were purified by HPLC to achieve > 98% purity and characterized by liquid chromatography-mass spectrometry (Table 1, Supplement S-1).…”
Section: Resultsmentioning
confidence: 99%
“…63,64 Circular dichroism (CD) experiments indicated that DNA duplexes containing N 6 -HB-dA, 1, N 6 -HMHP-dA, and N 6 , N 6 -DHB-dA adducts maintain a B-type DNA conformation. 28 Solution NMR structures of ( R , R ) and ( S , S )- N 6 , N 6 -DHB-dA and ( S )- N 6 -HB-dA containing DNA duplexes show that they are readily accommodated in the major groove of DNA. 65 Only small perturbations in base stacking and hydrogen bonding interactions were observed for ( S )- N 6 -HB-dA, while the presence of N 6 , N 6 -DHB-dA prevented its hydrogen bonding with thymidine in the opposite strand and disrupted stacking interactions of the adducted base with neighboring nucleotides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though two studies have found that both isomers reduce the melting point of duplex DNA to a similar extent, it was proposed that the different orientations of the hydroxyl groups on the DHB adducts could interact with DNA polymerases differently during TLS, thus leading to different outcomes. 44, 46 Investigation of the three stereoisomers of the DEB metabolites also found that the S,S -isomer is more cytotoxic and mutagenic than the meso - and R,R -isomers. 47 Our results here support the hypothesis that lesion stereospecificity modulates mutagenicity and genotoxicity, which has also been previously observed with the stereoisomers of three other BD adducts.…”
Section: Discussionmentioning
confidence: 99%
“…44 This decrease in stability was reflected in a similar decrease in melting points for both the R,R - and S,S -duplexes. 44, 46 Previously, we showed that all four bases can be inserted opposite R , R - N 6 , N 6 -DHB-dA when bypassed by TLS polymerases in vitro . 26 Here, we found that both N 6 , N 6 -DHB-dA lesions might induce low levels of A→G (~1%) and A→T (<1%) mutations.…”
Section: Discussionmentioning
confidence: 99%